Pembaruan Hukum Perlindungan Hak Atas Kesehatan Reproduksi Perempuan Di Indonesia - Nabila, Aulia; Desmawati, Yunita (Jurnal Hukum & Pembangunan, 2022)
The right to reproductive health is a part of the human rights regime that must be guaranteed by states. Provisions of women’s right to reproductive health in Indonesia are found separately in various legal instruments. However, the regulations are not comprehensive, vague, and gender-biased. Using human rights and feminist perspective, this article analyses the issues relating to women’s right to reproductive health in statutes and other legal instruments, as well as formulates a concept of revision of the law of women’s right to reproductive health. This article concludes that regulations regarding women’s right to reproductive health contain provisions that are vague and inconsistent with one another, are gender-biased, and are not human rights-based. The revision of regulations on the protection of women’s right to reproductive health can be conducted substantially and formally.